Patient Satisfaction Based on Responsiveness at the Kolaka Regency Health Center Using the American Customer Satisfaction Index (ACSI) Model - Syamsiah Nur; Sartini Risky; Wa Ode Nova Noviyanti Rachman (Magister Kesehatan Universitas Mandala Waluya, 2026)
Introduction: This study examines patient satisfaction levels at Kolaka Regency Community Health Centers using the American Customer Satisfaction Index (ACSI) model. The background of the study indicated patient satisfaction issues, particularly related to service responsiveness, identified through initial observations at four of the 14 health centers. The main issues included long waiting times, difficulty accessing information, and a lack of effective communication. The study aimed to evaluate patient satisfaction with a focus on the responsiveness of patient care at Kolaka Regency Community Health Centers. Method: This research employed a qualitative method with a case study design, involving 15 informants selected through purposive and snowball sampling techniques. Data collection was conducted through in-depth observation and triangulation, with data analysis using the N-VIVO application. Result: Despite positive aspects such as good communication and competent medical services, several areas still require improvement. Key challenges include long waiting times, the need for facility upgrades in some areas, and the need for efficiency in stock management and service times. Analysis using the ACSI Model revealed variations in patient satisfaction levels across various service aspects, with some community health centers performing better than others. Conclusion: Patient satisfaction levels at Kolaka Regency Community Health Centers vary and require improvement in several areas. Factors such as community health center accreditation, the number of healthcare workers, and the quality of facilities significantly influence patient satisfaction.